Finite Element Analysis for Investigating the Effects of Muscle Activation on Head-neck Injury Risks of Drivers Rear-ended by a Car after an Autonomous Emergency Braking - Masami Iwamoto; Yuko Nakahira; Daichi Kato (International Journal of Automotive Engineering, 2018)
Avoidance of frontal collisions by autonomous emergency braking (AEB) in sudden traffic jams has the potential to cause rear-end collisions by the following cars. In this study, finite element analyses using a human body model were performed to investigate how the muscle activations of drivers rear-ended by the following car could affect head-neck injury risks. Three muscle conditions of sleeping, relaxed, and braced drivers were assumed using a developed muscle controller. The simulation results suggest that vehicle systems that let drivers brace themselves at the onset of the AEB might be effective in reducing head-neck injury risks in this type of collisions.